Framing the Religious Dialogue Space: Learning from the Experience in North Sumatra - Ayunda Suci Aulia (Young Journal of Social Sciences and Humanities, 2025)
This research aims to explore the perspective of non-Muslim communities towards Muslim religious practices in North Sumatra. This study uses a qualitative approach with a letiratur study method with a phenomenological approach. The results of the study show that non-Muslim communities generally have different views on Muslim religious practices, ranging from tolerance to skepticism. It is hoped that this research will provide deeper insights into the dynamics of interfaith relations and encourage constructive dialogue between various communities in North Sumatra. Thus, the perception of non-Muslim communities towards Muslim religious practices reflects the diversity of views influenced by the local social and cultural context. So research can show that while many non-Muslims value and respect Muslim worship practices, there are also misconceptions and rejections of certain aspects that can and should not be upheld in the public sphere.